Biodiversity Indices and Medically Importance of Ticks in North Khorasan Province, Northeast of Iran - Kourosh Arzamani; Abedin Saghafipour; Seyed Ahmad Hashemi; Hassan Vatandoost; Mohammad Alavinia; Saber Raeghi; Zakyeh Telmadarraiy (Tehran University of Medical Sciences, 2021)
Background: Ticks are considered as the main vectors for the transmission of various pathogens such as relapsing fever and CCHF to humans. This study was investigated the biodiversity indices and medically importance of ticks in North Khorasan Province, Northeast of Iran during 2015-2019. Methods: Specimens were captured from infested ruminants including cows, sheep, and goats. Additionally, tick collections also were performed on non-domesticated creatures such as turtles, rodents, and hedgehogs. Specimens were identified using valid identification keys. Species diversity, species richness and evenness indices have been calculated to estimate species biodiversity of ticks. Results: A total of 1478 adult ticks were collected. The specimens were from two families: Ixodidae (90.05%) and Argasidae (9.95%), 6 genera and 17 species including: Rhipicephalus sanguineus (55.9%), Rhipicephalus bursa (13.4%), Hyalomma marginatum (9.5%), Hyalomma anatolicum (9.5%), Hyalomma asiaticum (0.2%), Hyalomma aegyptium (0.5%), Hyalomma scupense (1.3%), Hyalomma sp (1.2%), Haemaphysalis sulcata (0.7%), Haemaphysalis erinacea  (0.1%), Haemaphysalis inermis (0.1%), Haemaphysalis punctata  (0.2%), Haemaphysalis concinna (0.1% Boophilus annulatus (1.2), and Dermacentor marginatus (6.1%) among hard ticks as well as  Argas persicus (91.8%) and Argas reflexus (8.2%) amongst soft ticks. Rhipicephalus sanguineus, Rh. Bursa, Hy. marginatum and Hy. anatolicum were known as the most frequent species of hard ticks. Tick's species richness, Shannon diversity index and Simpson index in this area were S= 17, H'= 1.69, D= 0.294 respectively. Conclusion: Based on tick distribution veterinary authority, public health organizations and other officials should act for implementation of disease prevention.